Placental pathology associated with maternal age and maternal obesity in singleton pregnancy. (12th December 2022) - Zhang, Peilin; Haymar, Tsu; Al-Sayyed, Farah; Dygulski, Sylvia; Dygulska, Beata; Devi, Arooj; Lederman, Sanford; Salafia, Carolyn; Baergen, Rebecca
Abstract: Objective: Maternal age, maternal obesity and neonatal sex dimorphism are known to affect pregnancy and neonatal outcome. However, the effects of these factors on specific placental pathology are less well-documented. Study design: Clinical information, placental pathology and neonatal data from singleton delivery were collected at our hospital in March 2020 to October 2021 and correlation studies were performed. Results: A total 3, 119 singleton placentas were examined between March 2020 and October 2021 in conjunction with clinical information and neonatal birth data. Advanced maternal age (>35) was significantly associated with a variety of pregnancy complications and placental pathology including preeclampsia/pregnancy induced hypertension (Pre/PIH), gestational diabetes mellitus (GDM2), intrauterine growth restriction (IUGR), and increased maternal body mass index (BMI) at delivery. Maternal obesity (BMI >30 at the time of delivery) was significantly associated with a variety of clinical features and placental pathology including PRE/PIH, GDM2 and decidual vasculopathy (mural arterial hypertrophy). No specific placental pathology was associated with neonatal sex except for more maternal inflammatory response (MIR, chronic deciduitis) in neonates of male sex. Conclusion: Maternal age and maternal obesity were associated with not only clinical complications of pregnancy and neonatal birth weight but also specific placental pathology. Understanding the effects of maternal and environmental factors will help improve pregnancy outcome.